2020
DOI: 10.1590/0100-29452020515
|View full text |Cite
|
Sign up to set email alerts
|

Alternative budburst management in Campanha Gaúcha vineyards

Abstract: Seeking a less toxic alternative to budburst management than hydrogen cyanamide, doses of the mineral-organic product Erger® were tested in combination with calcium nitrate (Ca(NO3)2). The experiment was conducted in Santana do Livramento, southern Brazil, during the 2013/14 and 2014/15 growth cycles, in a ‘Merlot’ vineyard conducted in a vertical trellis system, pruned in double Guyot, with SO4 rootstock. Treatments were: Control (unsprayed); 5.0% Ca(NO3)2; 2.5% Erger® + 5.0% Ca(NO3)2; 5.0% Erger® + 5.0% Ca(N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…In agreement with these results, it has been observed in grapevine that, under subtropical conditions, plants sprayed with an Erger ® solution, and plants treated with hydrogen cyanamide (3.5–4.5%) solutions present similar vegetative bud break rates ( Fowler et al, 2020 ). Even so, both Erger ® and hydrogen cyanamide treatments exhibited a higher budburst (10–15%) than the control treatment ( Fowler et al, 2020 ; Rosa et al, 2020 ).…”
Section: Effects Of Agrochemicals On Endodormancy Releasementioning
confidence: 88%
See 1 more Smart Citation
“…In agreement with these results, it has been observed in grapevine that, under subtropical conditions, plants sprayed with an Erger ® solution, and plants treated with hydrogen cyanamide (3.5–4.5%) solutions present similar vegetative bud break rates ( Fowler et al, 2020 ). Even so, both Erger ® and hydrogen cyanamide treatments exhibited a higher budburst (10–15%) than the control treatment ( Fowler et al, 2020 ; Rosa et al, 2020 ).…”
Section: Effects Of Agrochemicals On Endodormancy Releasementioning
confidence: 88%
“…Different works in apple demonstrated that high concentrations of Erger R (5, 6, and 7%) were more efficient in advancing flowering time and increasing production (Hawerroth et al, 2010;Pasa et al, 2018). On the other hand, studies in grapevine and blackberry found no differences between low and high concentrations of Erger R solutions in terms of flowering time, fruit ripening or production (Segantini et al, 2015;Rosa et al, 2020). Similarly, in apple, no dissimilarities were observed between trees treated with 1 and 2% Syncron R solutions (Petri et al, 2016).…”
Section: Agrochemical Application Time and Concentrationmentioning
confidence: 96%
“…Increased budding and uniformity of budding have been observed in ‘Imperial Gala’, ‘Suprema’ and ‘Fuji’ apple trees when applying the organomineral fertilizer Erger G ® and hydrogen cyanamide (Hawerroth et al ., 2010 b ). An increase was reported in the formation of shoots in grapevines that received Erger G ® compared to water only (Rosa et al ., 2020). Thus, Erger G ® can increase the budding capacity in apple and grapevines, as observed here in the ‘Kampai’ peach tree.…”
Section: Discussionmentioning
confidence: 99%
“…La cianamida hidrogenada funciona en algunos frutales acorde con las condiciones específicas de temperatura y humedad que prevalezcan (bajas temperaturas y periodos de humedad prolongados), y su eficacia puede verse reducida si no se cumplen estos requisitos óptimos 34 . Si las condiciones ambientales no fueron favorables durante la aplicación de Dormex, es posible que no se haya observado un aumento significativo en el número de brotes 35 .…”
Section: Influencia De Cinco Concentraciones De Cianamida Hidrogenada...unclassified